Tanggung Jawab Notaris dalam Pembuatan Perjanjian Nominee Sebagai dasar Peralihan Hak Milik Atas Tanah oleh Warga Negara Asing di Indonesia - Dewi Masithoh; Dominikus Rato; Ermanto Fahamsyah (CV. Syntax Corporation Indonesia, 2021)
In general, the authority of a notary is contained in Article 15 of the UUJN, namely making an authentic deed. Regarding the authority of a notary in making a nominee deed, it is not specifically regulated in the article which results in legal uncertainty in the making of a nominee deed, especially related to the transfer of ownership rights to land by foreign citizens in Indonesia. The purpose of this study is to find out about future arrangements for the responsibility of the notary in making the nominee deed which is used as the basis for the transfer of property rights to land by foreign citizens in Indonesia. In this study, a normative juridical approach was used. The results of this study are the need for future arrangements regarding the making of the nominee deed which is used as the basis for buying and selling property rights by foreign citizens in Indonesia. studied using the theory of liability and the theory of legal certainty.